1989
DOI: 10.1177/00220345890680110501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Salivary Composition and Cortisol in Serum and Saliva in Man

Abstract: The effect of exercise on electrolytes and cortisol levels in serum and saliva was examined in 27 young, healthy male volunteers who performed graded submaximal cycle exercise for nine min at up to 85% of their age-predicted maximal heart rate. Seventeen men performed the Wingate anaerobic test for 30 s. A significant increase in pulse rate and systolic blood pressure and a decrease in diastolic blood pressure were found, and serum concentrations of Na+, K+, and lactate were significantly elevated immediately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 15 publications
2
21
0
2
Order By: Relevance
“…Therefore, the high concentration of salivary Cortisol accompanied by increase of saliva viscosity is the indicator of sympathetic nervous system activation [3]. The findings of this study are in line with findings of Ben-Aryeh et al [3] and KaciubaUscilko et al [17], who found that consecutive aerobic exercise and resistance exercise increase Cortisol concentration. Furthermore, the results of this study do not support the data given by O'Connor et al [33] and SariSarraf et al [37].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, the high concentration of salivary Cortisol accompanied by increase of saliva viscosity is the indicator of sympathetic nervous system activation [3]. The findings of this study are in line with findings of Ben-Aryeh et al [3] and KaciubaUscilko et al [17], who found that consecutive aerobic exercise and resistance exercise increase Cortisol concentration. Furthermore, the results of this study do not support the data given by O'Connor et al [33] and SariSarraf et al [37].…”
Section: Discussionsupporting
confidence: 91%
“…A study reported that Cortisol concentration increases due to continued exercises. These researchers reported that physical exercise could stimulate HPA, increase body temperature, increase Cortisol secretion, and the release of Cortisol from the carrier proteins [3]. Therefore, the high concentration of salivary Cortisol accompanied by increase of saliva viscosity is the indicator of sympathetic nervous system activation [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise provides an interesting model for study of the effects of milder dehydration. A number of studies have reported decreased salivary flow and compositional changes during exercise (Salminen & Konttinen, 1963;Shannon, 1967;Dawes, 1981;Bardon et al, 1983;Ben-Aryeh et al, 1989;Ljungberg et al, 1997;Walsh et al, 1999;Bishop et al, 2000). The results of these studies have been rather variable, which may reflect wide differences in exercise schedules and also, different methods of saliva collection.…”
Section: Salivary Factors and Dehydrationmentioning
confidence: 99%
“…Salivary Alpha-amylase [4]- [8] and cortisol [9]- [11] have both been assessed in numerous studies assessing the impact of both physical and psychological stressors on the levels of these hormones. Changes in glucose, lactate, glycerol, and NEFA levels during and following exercise are all potential indicators of altered fuel source availability [12]- [26].…”
Section: Introductionmentioning
confidence: 99%